GENDHING NDADI Musik dalam Angguk Non-Cerita di Kebumen - Rabimin Rabimin (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2002)
This point focuses on the explanation of musicality context that is generated by supernatural creed called ndadiin the Angguk folk art in the villages of Kebumen. It is intended to show the typicality of the musical environment.